Public Debate from the Perspective of Islamic Communication: An Analysis of Jidal Verses in Tafsir Al-Misbah - Adnan Adnan; Muhammad Syahrial Razali Ibrahim (Jurnal Impresi Indonesia, 2026)
This study examines public debate from an Islamic communication perspective, analyzing the jidal verses in the Tafsir Al-Misbah. The data collection method for this study was library research. The primary data was the Tafsir al-Misbah, while the secondary data consisted of a number of relevant literature, journals, books, articles, and books. The results indicate that the correct application of jidal ethics is expected to result in a positive and satisfactory conclusion to the debate for all parties, without causing hostility or harming any party. Public debate from an Islamic communication perspective, based on the Tafsir Al-Misbah, must be a constructive, ethical, dialogical process aimed at achieving mutual benefit, in accordance with the guidance of the Qur'an and Sunnah.